Factors associated with oral health service utilization among adults and older adults in China, 2015‐2016. Issue 1 (16th October 2019) - Xu, Mengru; Cheng, Menglin; Gao, Xiaoli; Wu, Huijing; Ding, Min; Zhang, Chunzi; Wang, Xing; Feng, Xiping; Tai, Baojun; Hu, Deyu; Lin, Huancai; Wang, Bo; et al.
Abstract: Objectives: To explore the factors associated with utilization of oral health services among Chinese adults and older adults according to the Andersen Behavior Model. Methods: Data from the 4th National Oral Health Survey (2015‐2016) in China were used. A total of 7206 people (3669 adults aged 35‐44 years and 3537 older adults aged 65‐74 years) were included in our analysis. Oral health service utilization in the past 12 months was the outcome variable. Explanatory variables were selected according to the Andersen Behavior Model. Descriptive statistics and bivariate associations (chi‐square tests) were analysed, followed by hierarchical Poisson regression models, which were conducted to determine the factors associated with oral health service utilization. Results: In total, 21.4% (95% CI: 19.4%‐23.7%) of adults (35‐44 years old) and 20.7% (95% CI: 18.6%‐22.9%) of older adults (65‐74 years old) utilized oral health services in the past 12 months. Nearly 80% of adults (78.7%, 95% CI: 74.0%‐82.7%) and more than 90% of older adults (93.7%, 95% CI: 91.0%‐95.6%) visited a dentist for treatment. Adults aged 35‐44 years old who were female (IRR: 1.15, 95% CI: 1.00‐1.33, P = .047), had good oral health knowledge and attitudes (IRR: 1.30, 95% CI: 1.06‐1.59, P = .011), perceived their oral health status as fair (IRR:1.51, 95% CI:1.24‐1.85, P < .001) or poor/very poor (IRR:2.52, 95% CI:2.01‐3.18, P < .001) and had a decayed, missing and filled teeth (DMFT) index >0 (IRR: 1.52, 95% CI: 1.11‐2.09, P = .009) were more likely to report dental visits in the past 12 months. Older adults who utilized oral health services tended to be female (IRR: 1.32, 95% CI: 1.09‐1.59, P = .004); to be covered by Urban Resident Basic Medical Insurance (URBMI) (IRR: 1.56, 95% CI: 1.18‐2.05, P = .002), Urban Employee Basic Medical Insurance (UEBMI) (IRR: 1.69, 95% CI: 1.32‐2.16, P < .001) or government medical insurance (GMI) (IRR: 1.03, 95% CI:1.01‐2.16, P = .044); to have a high education level (IRR: 1.37, 95% CI: 1.08‐1.74, P = .010); to have an income level in the 2nd tertile (IRR: 1.44, 95% CI: 1.13‐1.84, P = .003) or 3rd tertile (IRR:1.52, 95% CI:1.18‐1.95, P = .001); and to perceive their oral health status as poor or very poor (IRR: 1.53, 95% CI: 1.21‐1.95, P = .001). Conclusions: Sex and self‐perceived oral health status were associated with oral health utilization among Chinese population. Additionally, for older adults, education level, household income and insurance coverage were determinants of dental service use. These findings can aid in creating more targeted policies to increase the use of dental services by Chinese adults.